Біотеплова конвекція Дарсі–Брінкмана в пористому шарі, який обертається, насиченому ньютонівською рідиною, що містить гіротактичні мікроорганізми - Kopp, M.I.; Yanovsky, V.V. (Publishing house "Academperiodika", 2023)
The bio-thermal convection in a rotating layer of a porous medium saturated with a Newtonian fluid with gyrotactic microorganisms is studied on the basis of the Darcy–Brinkman model. A linear analysis of the bio-thermal convection is carried out using the Galerkin method for rigid-rigid boundary conditions. In a stationary regime, we obtained a dispersion equation with a relation between the thermal Rayleigh–Darcy number and the Rayleigh–Darcy number of bioconvection. The influence of the Peclet number, gyrotaxis, Darcy number, Rayleigh–Darcy number, cell eccentricity, and rotation parameter on bioconvective processes is analyzed and shown graphically. The results indicate that an increase in the rotation parameter (Taylor number) delays the onset of the bioconvection, whereas an increase in the cell eccentricity can stimulate the onset of the bioconvection.